Association Between Atopic Dermatitis and Cardiovascular Disease: A Nationwide Register-based Case-control Study from Sweden - Lina U. Ivert; Emma K. Johansson; Henrik Dal; Bernt Lindelöf; Carl-Fredrik Wahlgren; Maria Bradley (Medical Journals Sweden, 2019)
The associations between atopic dermatitis (AD) and cardiovascular disease (CVD) are debated. The aim of this study was to investigate the association between AD and coronary artery disease or ischaemic stroke in a nationwide, register-based, case-control study (104,832 AD cases, 1,022,435 controls) based on linkage of Swedish national register data between 1968 and 2016. Patients were classified as having severe AD if they had received systemic pharmacotherapy for AD or had been treated in a dermatological ward with AD as the main diagnosis. Other AD was classified as non-severe. After multivariable adjustments for comorbidities and socioeconomic status, overall AD was associated with angina pectoris (adjusted odds ratio (aOR) 1.13, 95% confidence interval (CI) 1.08-1.19), but among males with severe AD this association was not found, compared with the general population. Male non-severe AD was associated with myocardial infarction (OR 1.15, 95% CI 1.07-1.23). Severe AD was associated with ischaemic stroke, with similar estimates in men and women (aOR 1.19, 95% CI 1.07-1.33). Subgroup analyses among women indicated smoking as an important risk factor among severe cases. Diabetes mellitus, hyperlipidaemia, and hypertension were more prevalent in severe AD than in controls, and hyperlipidaemia and hypertension were also more prevalent in non-severe AD than in controls. In conclusion, in this study, AD was associated with CVD, and this should be kept in mind, especially when managing patients with severe AD.